Training is an important factor for community health workers in performing KOSPEN health screening activities in Malaysia : community health workers (KOSPEN) 2016 - Tania Gayle Robert Lourdes; Wan Shakira Rodzlan Hasani; Muhammad Fadhli Mohd Yusoff; Hamizatul Akmal Abd Hamid; Halizah Mat Rifin; Hasimah Ismail; Thamil Arasu Saminathan; Ling Miaw Yn, Jane Miaw Yn; Nur Liana Ab Majid; Mohd Ruhaizie Riyadzi; Ahzairin Ahmad; Rosnah Ramly (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Community health workers/volunteers (CHW) are health workers who are trained but do not possess a formal professional certificate. They are members of the community who live and work in that particular community. This study aimed to determine factors associated with not performing health screening activities by volunteers under KOSPEN; a community-based intervention programme, initiated by Ministry of Health Malaysia in October 2013. Data from the “Evaluation of the implementation of KOSPEN programme in Malaysia 2016” was used,a cross-sectional study which was carried out in randomly selected KOSPEN localities throughout Malaysia. The response rate was 94.9%. A pre-tested, self-administered questionnaire was used. Descriptive statistics andlogistic regression analysis was applied using Statistical Package for Social Sciences (SPSS) version 20. 700 volunteers were included in this study. Majority were female (65.7%), aged 50-59 years (30.9%), had secondary education (65.3%), employed (55.7%.) and married (80.4%). Several issues were identified by the volunteers; funding (47.2%), module content and comprehensibility (11.4% respectively), submitting returns (17%). Multivariate logistic regression showed that volunteers who never attended training (aOR 2.79; 95% CI:1.66, 4.67) and who felt the content of the training module was inadequate (aOR 2.693; 95% CI: 1.46, 4.98) were more likely did not perform screening activities in the community. Volunteers who were not trained and those who felt the content of the training module was inadequate did not carry out screening activities. These findings will be useful for stakeholders to make improvements to the programme for a more successful implementation.